1989
DOI: 10.1109/61.32638
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new type insulation diagnostic method for hot-line XLPE cables

Abstract: A new type insulation diagnostic system has been developed that makes automatic measurements of dielectric dissipation factor and dc component in a hot-line XLPE cable and makes an overall judgment of cable insulation deterioration. This system was tested on XLPE cables in hot-line conditions, the criteria for judgment of insulation deterioration were established based on the results o f measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…It is known that dielectric dissipation factor of cable insulation increases and its breakdown voltage decreases with the growth of water trees in the cable insulation [5], therefore one of the oldest techniques still frequently used for diagnosis insulation condition is the dielectric loss tangent measurement. The ratio of loss current to capacitive current (tanδ) is extremely important as property for showing the insulation loss.…”
Section: Diagnostic Methods Using Harmonic In Loss Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that dielectric dissipation factor of cable insulation increases and its breakdown voltage decreases with the growth of water trees in the cable insulation [5], therefore one of the oldest techniques still frequently used for diagnosis insulation condition is the dielectric loss tangent measurement. The ratio of loss current to capacitive current (tanδ) is extremely important as property for showing the insulation loss.…”
Section: Diagnostic Methods Using Harmonic In Loss Currentmentioning
confidence: 99%
“…Some methods examine the component in a de-energized condition while others are based on measurements carried out with an energized cable but without load. The reference [5] describes a synthesis of these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…They have excellent insulation properties and easy handling [1]. However, in spite of the excellent properties, it was found that water trees could occur in XLPE insulation depending on the environmental conditions, causing insulation deterioration, which may lead to insulation breakdown [2].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, when seeking practical ways for determining the final effects of water tree phenomena on cable degradation and observing studies about modeling and diagnosis, several researches, like those presented in [1][2][3][4][5][6][7][8][9], are intended to propose procedures to detect this kind of failure through the extraction of information from performance parameters that indicate the degradation level of the insulation layer of a power cable. The methods found in the aforementioned references have different approaches to ascertain power cable status.…”
Section: Introductionmentioning
confidence: 99%